1979
DOI: 10.1094/phyto-69-582
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Expression and Free Sterol and Fatty Acid Composition of Flue-cured Tobacco Plants Exposed to Ozone

Abstract: Two flue-cured tobacco cultivars, North Carolina 88 and Coker 86, were concentration but a decrease in the concentration of free sterols and fumigated with 0 to 0.30 ppm ozone (03) for 6 hr. Both cultivars were highly triglyceride fatty acids in all leaf tissues. These changes were not correlated sensitive to 03. Plants fumigated with concentrations of 03 greater than with injury ratings. It is postulated that triglyceride fatty acids and other 0.15 ppm displayed typical weather fleck symptoms. Fumigation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The effects of the pollutant on either the sterol concentration and composition have been early reported in several plants (Tomlinson and Rich 1971;Trevathan et al 1979;Grunwald and Endress 1985). In tobacco leaves, ozone fumigation enhances total lipid concentrations, but it decreases levels of FS and triglycerides (Trevathan et al 1979), whereas a higher amount of total phytosterols was reported in fumigated plants by other researchers (Menser et al 1977). Generally, exposure to high ozone concentrations (>12 L L −1 ) results in a decrease of free sterols (FS) and an increase in bound sterols (BS).…”
Section: Ozone and Isoprenoidsmentioning
confidence: 91%
See 1 more Smart Citation
“…The effects of the pollutant on either the sterol concentration and composition have been early reported in several plants (Tomlinson and Rich 1971;Trevathan et al 1979;Grunwald and Endress 1985). In tobacco leaves, ozone fumigation enhances total lipid concentrations, but it decreases levels of FS and triglycerides (Trevathan et al 1979), whereas a higher amount of total phytosterols was reported in fumigated plants by other researchers (Menser et al 1977). Generally, exposure to high ozone concentrations (>12 L L −1 ) results in a decrease of free sterols (FS) and an increase in bound sterols (BS).…”
Section: Ozone and Isoprenoidsmentioning
confidence: 91%
“…The effects of the pollutant on either the sterol concentration and composition have been early reported in several plants (Tomlinson and Rich 1971;Trevathan et al 1979;Grunwald and Endress 1985). The effects of the pollutant on either the sterol concentration and composition have been early reported in several plants (Tomlinson and Rich 1971;Trevathan et al 1979;Grunwald and Endress 1985).…”
Section: Ozone and Isoprenoidsmentioning
confidence: 99%
“…However, both animal viruses contain primarily cholesterol and cholesterol esters (McSharry & Wagner, 1971 ;Diringer et aL, 1973), while SYNV contains greater amounts of stigmasterol and fl-sitosterol than cholesterol. In tobacco leaves, cholesterol represents 5~ (Trevathan et al, 1979) to 10~ (Grunwald, 1975) of the individual sterols, but in isolated nuclear membranes the proportion of cholesterol reportedly varies from none (Philipp et al, 1976) to 90~ of the sterol fraction (Kemp & Mercer, 1968;Duperon et al, 1972). Therefore, with these discrepancies in mind, the presence of cholesterol in SYNV cannot be related to sites of assembly as has been done with some animal viruses (Compans & Klenk, 1979;Patzer et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…1979). Methanolysis of triacylglycerols and preparation of free sterol and free fatty acid derivatives were done as described by Trevathan et al (1979) (Pirone 1979 Trevathan and Moore (1911) and is similar to that noted by Pirone and Davis (1977) with tobacco-vein-mottling virus, but differed from that reported by Richardson et al (1968) and Baur et al (1961), who found no effect of TMV on sterol content of Samsun tobacco. However, these authors initially hydrolyzed tobacco samples with 2 N HCI fbr 3 h, a Procedure which probably released bound sterols present as steryl glycosides (Bradford et (Matthews 1970).…”
Section: Methodsmentioning
confidence: 99%
“…1979). Methanolysis of triacylglycerols and preparation of free sterol and free fatty acid derivatives were done as described by Trevathan et al (1979). Samples…”
mentioning
confidence: 99%